2009
DOI: 10.1016/j.jpain.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxytocin and Prolactin on Stress-Induced Bladder Hypersensitivity in Female Rats

Abstract: Anecdotal evidence suggests that chronic bladder pain improves while breastfeeding. The present study sought to identify potential mechanisms for such a phenomenon by investigating the effects of the lactogenic hormones prolactin (PL) and oxytocin (OXY) in a rat model of bladder nociception. Lactating rats were less sensitive to urinary bladder distension (UBD) than controls. In investigating potential antinociceptive and anxiolytic roles for these hormones, we found exposure to a footshock paradigm (STRESS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 55 publications
(71 reference statements)
2
27
0
2
Order By: Relevance
“…Preclinical studies have indicated a potential analgesic role for oxytocin in pain associated with the bladder 3,5 , and it was anticipated that similar results would be seen in the present study. While no significant effect of oxytocin on pain has been observed to date, there is a trend in that direction, and a larger sample size is still needed.…”
Section: Body Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Preclinical studies have indicated a potential analgesic role for oxytocin in pain associated with the bladder 3,5 , and it was anticipated that similar results would be seen in the present study. While no significant effect of oxytocin on pain has been observed to date, there is a trend in that direction, and a larger sample size is still needed.…”
Section: Body Resultssupporting
confidence: 83%
“…No differences in the two treatments conditions were evident by the 24 hour time point. These findings are consistent with reports of decreased anxiety behaviors in numerous animal studies 2,3,[7][8][9][10][11] . Recent clinical studies have also reported similar anxiolytic-like effects of oxytocin 1,4,6 .…”
Section: Verbal Pain Reportsupporting
confidence: 92%
“…Therefore, patients diagnosed with IC/BPS and other functional urinary tract disorders may have abnormalities in the HPA axis, and stress could contribute to bladder symptoms, including frequency, urgency, and/or pain, reported by these patient populations (47). The pathophysiology underlying stress-induced effects on micturition reflex function remain undetermined.The most well-established animal models of stress used to examine effects on urinary bladder structure and function include the resident-intruder model (15,22,74), immobilization stress (10, 11), water avoidance stress (WAS) (14,54,55,62), and electrical footshock (7,55). Although these stress paradigms produce bladder dysfunction and target tissue (i.e., urinary bladder) abnormalities similar to conditions like IC/BPS, the data in some cases are conflicting, and the stress models used in these studies may not be relevant to the variety of life stressors experienced by humans on a daily basis.…”
mentioning
confidence: 99%
“…OT tedavisinin serum kortizol seviyesini düşürmesi nedeniyle bu hormonun stres üzerinde azaltıcı etkisi olduğu düşünülmektedir. Black ve arkadaşları, dişi sıçanlarda ağrı ve kaygı stresleri ile oluşturdukları İS modelinde, OT hormonunun mesane ağrısı üzerinde anksiyolitik ve analjezik etki gösterdiğini tespit etmişlerdir (15). Bizim çalışmamızda ise OT hormonunun erkek sıçanlarda İS'in sebep olduğu morfolojik ve biyokimyasal hasarlar üzerinde tedavi edici rolü gözlenmiştir.…”
Section: Discussionunclassified
“…Ayrıca, bu hormonun bazı interlökin salınımının inhibisyonuyla immün ve enflamatuvar süreçleri düzenleyerek antienflamatuvar etki gösterdiği de ortaya konulmuştur (13,14). Black ve ark., sistemik OT'nin analjezik ve anksiyolitik etkilerine sahip olduğunu ve stresin sebep olduğu kronik ağrı sendromunda oldukça kullanışlı bir ajan olabileceğini ileri sürmüşlerdir (15). Literatür incelemesinde kronik strese bağlı İS modellerinde çoğunlukla dişi deney hayvanları kullanılmış olup, stresin erkek cinsiyete ait mesane dokusundaki etkileri üzerinde çok fazla çalışılmamıştır.…”
Section: Original Research öZetunclassified